Agricultural Land Use Pattern: Exploring the Agricultural Landscape of Amroha in Uttar Pradesh (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The core of Uttar Pradesh's economy is agriculture. In this area, traditional agricultural practicespredominated until relatively recently, but they are gradually changing as a result of the introduction ofnew inventions and scientific techniques. Over 75 of Uttar Pradesh's working population is employed inagriculture. This region contains essential agricultural inputs and resources that increase agriculturaloutput, provide food, and a variety of industrial raw materials to fuel the agro-based industries. A study ofagricultural land usage is obviously important in this area, as agriculture dominates the local economy.The primary goals of this essay are to outline the potential of agro-based enterprises and to describe thepattern of agricultural land usage in the Amroha district of Uttar Pradesh.